Pengembangan Sistem Informasi Monitoring Transaksi Gas Elpiji PT. Amrin Jami Indonesia Tigaraksa - Dien, Albert Yusuf; Rais, Nurlaila Suci Rahayu; Rechandini, Anggi (Technomedia Journal, 2018)
Elpiji 3 kg gas needs is one of the mandatory things for household needs especially for the needs of Small and Medium Enterprises (SMEs). Therefore PT. Amrin Jami Indonesia located in Tigaraksa became one of elpiji 3Kg gas agents to meet the gas needs of Tigaraksa residents and surrounding areas. The trade with a national-scale company and goods sold are subsidized, of course, there must be a record in the case of transactions, whether it is the recording of each gas base to the household. Although manual recording has been done, but due to the location of the remote base has caused difficulties in terms of transaction control and evaluation. Therefore the need for a system that runs Online so it can do 24 hour control and evaluation and reduce the number of base meetings in which each base already has its own busyness. Online system to be created includes the allocation of elpiji gas cylinders to each base, transactions at each base to retailers, SMEs, and households. In each transaction requires data such as the buyer's name, ID number, phone number, and number of tubes purchased. The research method that will be used is the development method starting from research, planning, testing, and evaluation. This Registration shall be conducted so that there will be no mistake in the transaction especially regarding the distribution of this subsidized goods from any form of criminal act such as oplosan gas. Keywords: Information System, Elpiji, Transaction